Marriage, cohabitation and commitment - Murat Iyigun (Institute for the Study of Labor (IZA), 2009)
This paper combines partner matching with an intra-household allocation model where couples decide if they want to marry or cohabitate. Marriage encourages but does not ensure a higher level of spousal commitment, which in turn can generate a larger marital surplus. Individuals' marital preferences and commitment costs vary, and sorting equilibria are based on individuals' marital preferences and propensity to commit. In all equilibria, some married couples are able to cooperate and operate efficiently, but some married and all cohabiting couples act with limited commitment and non-cooperatively. When spousal marital commitment costs are gender symmetric, there is a pure-sorting equilibrium in which all partners who prefer to act with commitment in marriage are matched with someone who has the same preference. In such an equilibrium, the benefits of marital commitment accrue to both partners. When commitment costs are not gender neutral, there can also be mixed-matching equilibria in which a partner who is willing to act with commitment in marriage is matched with someone who is not. In all such equilibria, the benefits of marital commitment accrue only to those men or women who are in short supply. Consequently, a shortage of men (women) who can maritally commit makes all women (men) worse off and materially indifferent between marriage or cohabitation. An excess supply of men who prefer marriage not only reduces the marriage incentives of men and raises those of women, but also the marital commitment incentives of men. As a corollary, if the gains from marriage fall, not only will more individuals choose to cohabitate but more married couples will act non-cooperatively.
urn:nbn:de:101:1-20090909423
Keywords: C78; D61; D70; 300; Collective model; intra-household bargaining; modes of partnership choice; Ehe; Lebensgemeinschaft; Haushaltsökonomik; Familienökonomik; Theorie